Epigenetic dynamics during flowering plant reproduction: evidence for reprogramming?. Issue 1 (11th May 2019) - Gehring, Mary
Abstract : Summary: Over the last 10 yr there have been major advances in documenting and understanding dynamic changes to DNA methylation, small RNAs, chromatin modifications and chromatin structure that accompany reproductive development in flowering plants, from germline specification to seed maturation. Here I highlight recent advances in the field, mostly made possible by microscopic analysis of epigenetic states or by the ability to isolate specific cell types or tissues and apply omics approaches. I consider in which contexts there is potentially reprogramming vs maintenance or reinforcement of epigenetic states.